BOOK REVIEW: THE POWER OF GEOGRAPHY: TEN MAPS THAT REVEAL THE FUTURE OF OUR WORLD (Margalla Papers, 2022)
The power of geography is all about the geographical significance of a state. It is not every time that major powers will decide the fate of all states; sometimes geography, whether human, political or environmental, all play a significant role in standardizing the relative power capability of states. Marshall claims that smaller states with geographical significance also have much say in international politics and changing world environment. The book discusses states, regions and, most importantly, space that will impact international politics in the coming era. Author has discussed five geographically important regions and states within these regions. Indo-Pacific through Australia, Africa through The Sahel and Ethiopia, Europe through the UK, Turkey, Greece and Spain, the Middle East through Iran and Saudi Arabia, and lastly, space will be the focus of the coming generation in international politics. For these entities, geography has proven a power.